2019
DOI: 10.1001/jamaneurol.2019.2478
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the Central Vein Sign as a Diagnostic Imaging Biomarker in Multiple Sclerosis

Abstract: for the MAGNIMS Study Group IMPORTANCE The central vein sign has been proposed as a specific imaging biomarker for distinguishing between multiple sclerosis (MS) and not MS, mainly based on findings from ultrahigh-field magnetic resonance imaging (MRI) studies. The diagnostic value of the central vein sign in a multicenter setting with a variety of clinical 3 tesla (T) MRI protocols, however, remains unknown. OBJECTIVE To evaluate the sensitivity and specificity of various central vein sign lesion criteria for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
148
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(171 citation statements)
references
References 38 publications
15
148
2
6
Order By: Relevance
“…8 A recent large, multicentre study included patients with CISs and relapsing-remitting multiple sclerosis (RRMS) from observational studies or neuroimaging research databases. 4 This study confirmed the three-lesion rule as showing the most balanced diagnostic properties (61.9% sensitivity and 89.0% specificity) when assessing different absolute lesion number thresholds to differentiate MS from non-MS. However, despite including patients with CIS and early RRMS, the mean disease duration was 7 years, it was a cross-sectional study, and not all data originated from observational cohorts.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…8 A recent large, multicentre study included patients with CISs and relapsing-remitting multiple sclerosis (RRMS) from observational studies or neuroimaging research databases. 4 This study confirmed the three-lesion rule as showing the most balanced diagnostic properties (61.9% sensitivity and 89.0% specificity) when assessing different absolute lesion number thresholds to differentiate MS from non-MS. However, despite including patients with CIS and early RRMS, the mean disease duration was 7 years, it was a cross-sectional study, and not all data originated from observational cohorts.…”
supporting
confidence: 73%
“…The central vein sign (CVS) has been proposed as a specific biomarker for multiple sclerosis (MS). 1 Although best visualized at ultra-high field magnetic resonance imaging (MRI), recent evidence demonstrates that the CVS can be detected with MRI at 3.0 and 1.5 T, [2][3][4] making it potentially useful in the clinical practice. The high specificity of the CVS in MS derives from comparisons with other neurological diseases with focal white matter hyperintensities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are particularly relevant considering that recent studies using manual CVS classification at clinical field strengths have shown potential for application of the CVS imaging biomarker in clinical practice . Importantly, the most recent international panel for MS diagnosis called for further research on this topic before considering inclusion of the CVS in future MS diagnostic criteria .…”
Section: Discussionmentioning
confidence: 81%
“…Today, the vein at the center of WM lesions can be imaged in vivo using optimized susceptibility‐based MRI sequences, and several studies have shown that the CVS can accurately distinguish MS from other disorders showing similar T2 hyperintensities on MRI . Results from a recent multicenter study suggest that the diagnostic performance of this CVS biomarker at clinical field strengths is highly dependent on the type of susceptibility‐based MRI sequence used . In this context, recent data from our group using an optimized three‐dimensional (3D) T2*‐weighted segmented echo‐planar imaging (T2*‐EPI) sequence at clinical field strengths have shown that the CVS can efficiently discriminate between MS and inflammatory vasculopathies of the CNS and that this imaging biomarker can accurately predict an MS diagnosis in patients harboring atypical features for the disease …”
Section: Introductionmentioning
confidence: 99%